CONTINUING EDUCATION IN HEALTH THE PERSPECTIVE OF MEMBERS OF THE COMMITTEES OF INTEGRATION SERVICE-LEARNING - Luiz Anildo Anacleto da Silva; Marinês Tambara Leite; Leila Mariza Hildebrandt; Camila Pinno (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976928476 Aim: to learn how Committees on Teaching and Service Integration members comprehend factors that facilitate or limit the development and provision of regional plans and the characteristics of the educational proposals, related to employee participation in setting educational proposals, Method: qualitative, descriptive and exploratory, attended by twenty people. Data analysis followed the proposed content analysis. Results: the scenario indicates incipient participation and involvement in the definition of education plans. Among risk factors contained in the structuring of services, participation and institutional involvement. The constraint refers to the proposed fragmentation and insufficient participation and / or ignorance of managers. Two educational modalities prevail: the reiterative style and technical and the other innovation and transformation. Conclusion: there are peculiarities to be overcome, however, the scenario of continuing health education is changing.